Moderne Arbeit in der Bundesverwaltun Digital, flexibel und gesund - Sonntag, Karlheinz (2022)
Progressive digital transformation, increased dynamics of change in organizations, and the consequences of demographic change have reached employees in administrations at the federal, state, and local levels with vehemence. This volume provides answers to the question of how to deal with this and how specialists and managers can be prepared to meet the challenges of modern flexible and de-bureaucratized work in a healthy, competent and motivated manner. This book goes beyond the mere reporting of a research project and aims to provide up-to-date design knowledge of modern future-oriented administrative work.